Volumetric design of bituminous mixtures – Portuguese experience - Gardete, Dinis (2008)
In Portugal the Marshall method is used for bituminous mixtures design. However, methods based on empirical tests, such as the Marshall method or the Hveem method, are known to have major drawbacks. It is expected that the volumetric design of bituminous mixtures will replace these methods upgrading bituminous mixture design. In the volumetric design of bituminous mixtures specimens are prepared using the gyratory compactor and their volumetric proprieties are used to determine the optimum binder content. This volumetric design is the core of the first stage, and many times the only stage, of bituminous mixture design in the USA and Australia, for instance. The definition of design values that can simulate the field behavior of the bituminous mixtures is important. However the definition of the design values has to take in account the bituminous mixtures proprieties, traffic levels, temperatures and the existing experience with the behavior of the bituminous mixtures. In this work a study was carry on the application of gyratory compactor to common Portuguese bituminous mixtures taking in account the experience of other countries, the current practice and the capability to use this equipment as a base for volumetric design. The limit values for the volumetric design parameters such as the volume of voids or the VMA are also analyzed. New possible improvements in the known design procedures are discussed. Direction lines are draw regarding the application of volumetric design to the bituminous mixtures used in Portugal.